Analisis Citra Satelit MTSAT dan TRMM menggunakan Software ER MAPPER, SATAID dan PANOPLY saat Kejadian Curah Hujan Ekstrim di Wilayah Manado, 16 Februari 2013: ovvria Sagita, Ratih Prasetya - Novvria Sagita, Novvria Sagita; Ratih Prasetya, Ratih Prasetya (Jurnal Fisika dan Aplikasinya, 2025)
The amount of rainfall recorded in Sam ratulangi Meteorological station on February 16th 2013 was 237,5 mm which indicats an extreme rainfall. On the next day, February 17th 2013, there was flooding in the area of Manado. The pixel value analysis of MTSAT (Multifunctional Transport Satellites) on IR(infra red) channel by using ER Mapper software shows an increase pixel value at 08.00 UTC that indicats low temperature at the top clouds. The analysis of satellite image on IR channel by using SATAID software (GMSLPW) shows that the cloud was covering most of Manado area starting at 11.00 UTC, and analysis of satellite image on Visible channel shows the highest value of albedo index which reach 0.49 at 05.00 UTC. The observation of rainfall accumulation by using TRMM (Tropical Rainfall Measuring Mission) software on February 16th 2013 reached 205.2 mm.